EFEKTIVITAS PERMAINAN KOTAK KATA CERIA DALAM PENGENALAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA DINI DI TAMAN KANAKKANAK BHAKTI BUNDA PADANG - Marisa, Usnaul; Syofriend, Yul; Muryanti, Elise; Syafnita, Tisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The issue this study attempts to solve is children's low beginning reading proficiency, which is demonstrated by their inability to recognize letters, recognize symbols, and create simple words due to boring and uninteresting teaching techniques. The purpose of this study is to determine whether the